Stress, senescence, and specialized metabolites in bryophytes. (8th March 2022) - Kulshrestha, Samarth; Jibran, Rubina; van Klink, John W; Zhou, Yanfei; Brummell, David A; Albert, Nick W; Schwinn, Kathy E; Chagné, David; Landi, Marco; Bowman, John L; Davies, Kevin M
Abstract: Life on land exposes plants to varied abiotic and biotic environmental stresses. These environmental drivers contributed to a large expansion of metabolic capabilities during land plant evolution and species diversification. In this review we summarize knowledge on how the specialized metabolite pathways of bryophytes may contribute to stress tolerance capabilities. Bryophytes are the non-tracheophyte land plant group (comprising the hornworts, liverworts, and mosses) and rapidly diversified following the colonization of land. Mosses and liverworts have as wide a distribution as flowering plants with regard to available environments, able to grow in polar regions through to hot desert landscapes. Yet in contrast to flowering plants, for which the biosynthetic pathways, transcriptional regulation, and compound function of stress tolerance-related metabolite pathways have been extensively characterized, it is only recently that similar data have become available for bryophytes. The bryophyte data are compared with those available for angiosperms, including examining how the differing plant forms of bryophytes and angiosperms may influence specialized metabolite diversity and function. The involvement of stress-induced specialized metabolites in senescence and nutrient response pathways is also discussed. Abstract : We review how specialized metabolites help plants cope with the abiotic and biotic stresses of the terrestrial environment, and compare emerging knowledge on bryophytes with that available for angiosperms.